Ulkus Marjolin yang Berkembang dari Ulkus Trofik Kronis pada Pasien Kusta - Adniana Nareswari; Harijono Kariosentono; Nugrohoaji Dharmawan; Muhammad Eko Irawanto; Nurrachmat Mulianto (MEDICINUS, 2021)
Marjolin’s ulcer is a malignant complication of chronic ulcer. Changes in ulcer lesions to malignancy can be caused by chronic irritation, infection, decreased vascular variation, and increased expression of proto-oncogene. The most common histopathological form of Marjolin's ulcer is squamous cell carcinoma. A 55-year-old man, complaining of a protruding wound on his left hand that has not healed since three years ago. The patient was diagnosed with leprosy 30 years ago with a history of incomplete treatment. On physical examination, the left palmar region showed solitary ulcer, ±10x8x1.5 cm in size, nodular surface, reddish, hard consistency, with bulging and irregular edge. Slit-skin smear (SSS) examination with Ziehl-Neelsen staining found abundant acid-fast bacilli. Histopathological examination of the ulcer edge shows appearance of epithelial tumor, with differentiated epidermal cells invading the dermis, tumor cells arranged focally and concentrically with a mass of keratin appeared as horn pearl cells. Fite-Faraco staining found abundant M. leprae acid-fast bacilli. Based on the patient’s medical history and clinical examination, patient was diagnosed with Marjolin's ulcer in multibacillary (MB) leprosy. Patient was treated with MB multidrug therapy for 12 months and below-wrist amputation.